Ultrafine-grained Mg–Zn–Yb–Zr alloy with simultaneously improved strength and ductility processed by axisymmetric hot extrusion. (March 2020) - Li, Lu; Wang, Yu; Zhang, Cuncai; Wang, Tao; Lv, Hao; Yu, Wenbin
Abstract: The evolution of microstructure and mechanical properties of Mg–6.0 Zn–2.0 Yb–0.5 Zr alloy during axisymmetric hot extrusion was tracked. The initial bimodal-grained sample with most nanoprecipitates presented an ultra-high ultimate tensile strength (UTS) of 436 MPa and a lower elongation (EL) of 14.1% along the extrusion direction (ED), while the fully recrystallized ultrafine-grained (UG) sample with less precipitates exhibited a favorable balance in UTS and EL of 393 MPa and 19.1%, respectively. The Mg–Zn–Yb thermostable nanoprecipitates present in the alloy improved its strength, and the tilted weak texture that was rarely observed in the axisymmetric extrusion contributed to the ductility enhancement. The present work is likely to provide the fundamental insight into the underlying mechanisms of achieving the strength-ductility synergy via precipitation and texture tailoring in a newly developed Yb-alloyed Mg alloy with conventional and readily available processing technology. Graphical abstract: Image 1 Highlights: Yb promotes the c -axis of most grains inclined to the extrusion direction. A tilted weak texture contributes to the ductility enhancement. Thermal stable Mg–Zn–Yb nanoprecipitates improve its strength. Tailored precipitation and texture improve strength and ductility.